The observed effects of money laundering for Jamaica - Gray-Farquharson, Naderah ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Provides a relevant definition of money laundering, with special reference to the Caribbean. Identifies the factors that make the Caribbean an increasing destination for laundering money. Seeks to determine empirically the impact of money laundering on the financial sector.